2017
DOI: 10.1186/s13063-017-2205-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of action observation therapy and mirror therapy after stroke on rehabilitation outcomes and neural mechanisms by MEG: study protocol for a randomized controlled trial

Abstract: BackgroundLoss of upper-extremity motor function is one of the most debilitating deficits following stroke. Two promising treatment approaches, action observation therapy (AOT) and mirror therapy (MT), aim to enhance motor learning and promote neural reorganization in patients through different afferent inputs and patterns of visual feedback. Both approaches involve different patterns of motor observation, imitation, and execution but share some similar neural bases of the mirror neuron system. AOT and MT used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Therefore, these two modalities can be viewed as optional motor priming tools for stroke rehabilitation. However, there is still a lack of studies directly comparing the clinical improvements and the pattern of neuroplasticity induced by MVF and AO [ 69 ] and whether or not the activation pattern is congruent with the clinical improvements in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these two modalities can be viewed as optional motor priming tools for stroke rehabilitation. However, there is still a lack of studies directly comparing the clinical improvements and the pattern of neuroplasticity induced by MVF and AO [ 69 ] and whether or not the activation pattern is congruent with the clinical improvements in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…This was a three-arm, single-blind, randomized controlled trial. We followed the methods of Shih et al which is Methods/design of this trial [31]. However, given the limited funding and study resources, we only applied and analysed some secondary outcomes of the published study protocol [31] in this pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the methods of Shih et al which is Methods/design of this trial [31]. However, given the limited funding and study resources, we only applied and analysed some secondary outcomes of the published study protocol [31] in this pilot study. Each participant received intervention for 15 training sessions (60 minutes/day, 5 days/week for 3 weeks).…”
Section: Methodsmentioning
confidence: 99%
“…Several works found that action observation training (AOT), which includes observation and execution of an action (Ertelt & Binkofski, ) and is evidently based on the stimulation of the MN system (Shih et al, ), has a positive effect on PD rehabilitation. During a typical rehabilitation session, patients must observe a specific daily action presented through a video clip on the computer screen and then perform what they have observed.…”
Section: Mirror Neurons and Neurodegenerative Diseasesmentioning
confidence: 99%